Lire / consulter les cartes – reproductions numériques et outils de navigation - Jean-Luc Arnaud (In Situ)
This paper deals with the digital reproduction of map heritage. It is the result of a double experience: that of creation and management of the programme entitled CartoMundi - Online enhancement of the cartographic heritage and that of several years’ work in the field of cartography and picture history. In relation to texts, the specificities of cartographic material mobilise particular cognitive processes that are at the origins of a particular mode of investigation. We do not actually read a map, we consult it. And, we do not consult a map a priori, we consult it in order to answer questions. This is the context in which this paper examines the issues raised by digital reproductions and research tools into the catalogues. It shows that cartographical material cannot be recorded as simple images. On the contrary, its treatment through geographic information systems offers still unexploited opportunities that deserve larger development.